Prefabricated Flaps: Identification of Microcirculation Structure and Supercharging Technique Improving Survival Area - Xu, Heng; Feng, Shaoqing; Xia, Yimeng; Steinberger, Zvi; Xi, Wenjing; Fang, Hongwei; Li, Zhiwei; Xie, Yixin; Zhang, Yixin (Journal of Reconstructive Microsurgery, 2017)
Background Microcirculation is an important factor frequently overlooked when studying the survival of prefabricated flaps. In the current study, we use different prefabrication techniques for characterizing microcirculation within the flap, with the goal of finding an effective way to improve its survival area.Methods An abdominal prefabricated flap rodent model was created using a two-stage operation. All rats were randomly divided into six groups (n = 10/group): group A, prefabricated femoral vessels; group B, prefabricated femoral artery with a connected superficial inferior epigastric vein (SIEV); group C, connected superficial inferior epigastric artery (SIEA) with a prefabricated femoral vein; group D was similar to group A along with a prefabricated SIEA, and group E was similar to group A along with a prefabricated SIEV; and group F acted as a control group and consisted of an axial flap nourished by superficial inferior epigastric vessels. Flaps were assessed for survival area, blood perfusion area, and capillary density using macroscopic analysis, near-infrared fluorescence imaging (NIFI), and histology.Results The survival area was not significantly different when comparing groups B to C, and D to E. The survival area of groups D and E was larger than that of groups B and C. Groups B through E had a smaller survival area in comparison to group F and a larger survival area than group A. NIFI were consistent with the macroscopic outcomes. The capillary density was not significantly different between groups A to C and groups D to F.Conclusion Both arterial and venous supercharging could potentially improve the survival area of prefabricated flaps.
Keywords: prefabricated flaps; microcirculation; supercharging